Reel to real : race, sex, and class at the movies - Hooks, Bell. (New York : Routledge, 1996)
"Although it may not be the goal of filmmaker, most of us learn something when we watch movies. They make us think. They make us feel. Occasionally they have the power to transform lives. In Reel to Real, Bell Hooks talks back to films she has watched as a way to engage the pedagogy of cinema - how film teaches its audience."--BOOK JACKET. "Bell Hooks comes to film not as a film critic but as a cultural critic, fascinated by the issues movies raise - the way cinema depicts race, sex, and class. Reel to Real brings together Hooks's classic essays (on Paris is Burning or Spike Lee's She's Gotta Have it) with her newer work on such films as Girl 6, Pulp Fiction, Crooklyn, and Waiting to Exhale, and her thoughts on the world of independent cinema. Her conversations with filmmakers Charles Burnett, Julie Dash, and Arthur Jaffa are linked with critical essays to show how cinema can function subversively, even as it maintains the status quo."--BOOK JACKET.
Although it may not be the goal of filmmaker, most of us learn something when we watch movies. They make us think. They make us feel. Occasionally they have the power to transform lives. In Reel to Real, Bell Hooks talks back to films she has watched as a way to engage the pedagogy of cinema - how film teaches its audience. Bell Hooks comes to film not as a film critic but as a cultural critic, fascinated by the issues movies raise - the way cinema depicts race, sex, and class. Reel to Real brings together Hooks's classic essays (on Paris is Burning or Spike Lee's She's Gotta Have it) with her newer work on such films as Girl 6, Pulp Fiction, Crooklyn, and Waiting to Exhale, and her thoughts on the world of independent cinema. Her conversations with filmmakers Charles Burnett, Julie Dash, and Arthur Jaffa are linked with critical essays to show how cinema can function subversively, even as it maintains the status quo.
19. The oppositional gaze: black female spectators -- 20. Is paris burning? -- 21. "Whose pussy is this?" a feminist comment.
Includes index.
Keywords: Motion pictures -- Social aspects -- United States; Motion pictures -- Political aspects -- United States; Motion picture producers and directors -- United States -- Interviews; African American motion picture producers and directors -- Interviews